Prevalence of different palatal rugae patterns in a sample Lucknow population - Mohammed Asdullah; Srinivas Kandakurti; Arti S Sachdev; Vasu S Saxena; Ratnakar Pamula; Jyoti Gupta (Wolters Kluwer Medknow Publications, 2014)
Introduction: Palatoscopy is the study of palatal rugae pattern and it can be used to establish the identity of a person. The rugae are unique internal structures protected by the lips, buccal pad of fat and teeth that resist decomposition, thus serving an important role in forensic identification. The appearance of palatal rugae is constant, as they do not demonstrate changes after the completion of growth of the individual, thus increasing its utility as a personal identification tool. Aims and Objectives: To study the prevalence of different palatal rugae patterns in a sample of Lucknow, India population. Materials and Methods: The study comprised 100 healthy (50 males and 50 females) subjects of age between 18 and 40 years, who were randomly selected. In this study we used the classification of rugae patterns suggested by Kapali et al. (straight, curved, wavy andcircular), and Thomas and Kotze (unification and nonspecific). Results: The mean rugae number in females was slightly more than males. The most prevalent forms in both genders were curved type followed by wavy, straight and diverging types. Straight and curved forms were significantly more in numbers in females than males. Conclusion: This is a preliminary study on a localized Indian population. Scope still exists for further studies to determine gender as well as personal identification. We believe that rugae can be used as a reliable guide in forensic identification.